A Case Report of Rare Type of Chorea with Hypoxic-Ischemic Insult. - Roohi Kolte; Dr Ganna Gnyloskurenko (University Library System, University of Pittsburgh, 2022)
CASE REPORT A 10-year-old male child came with complaints of involuntary moments of the right upper and lower limb and slurred speech for about 2 days. There was no fever, lethargy, altered sensorium, convulsions, vomiting, loose motions, or joint pain. The history of similar complaints, hospitalization before was absent. There were determined Bp-104/68, Pulse- 96/min, RR-22/min, SpO2-99%, and temperature 36.6 0 C. Motor examination, and neurological examination were normal. Tests like CBC, CRP, ESR, solubility test, Antistreptolysin O (ASO) titer, INR, LFT, KFT were normal. MRI brain was performed and results showed multiple T2/ FLAIR hyper-intense foci in the bilateral head of caudate nucleus, (left > right) bilateral dorsal thalamus, deep whited matter of bilateral perirolantoic cortex. The hypo-intense T1W1 zones were found. Mild atrophy of the right caudate nucleus was noted. The above MRI images suggested sequelae to hypoxic ischemic insult. Injection phenobarbitone 440mg in 20 ml NS over 20 min, IV stat (20), tab haloperidol 0.25 mg, syrup multivitamin 5 ml, syrup calcium 5 ml, tab of folic acid (5mg) was given after admission. The abnormal movements were gradually improved and slurred speech decreased. After discharge, the patient continued medical treatment with Tab haloperidol 0.25 mg BD, a multivitamin tablet, and calcium phosphate 500mg BD for 14 days. Conclusion: Movement disorders have been associated with hypoperfusion and hypofunction in the caudate nucleus which was determined by cerebral imaging. The patient should be under the observation of a neurologist to prevent complications.